Case Report: Steroids for diabetic myonecrosis in ESKD: an unconventional treatment with unexpected success - Tse, Justin David; Laller, Sristhi; Kharait, Sourabh (Frontiers in Nephrology, 2025)
IntroductionMyonecrosis is a rare but serious complication of diabetes, particularly in patients with end-stage kidney disease (ESKD), characterized by ischemic necrosis of the skeletal muscles. Its diagnosis is often delayed due to overlapping presentations with cellulitis or deep vein thrombosis. Treatment is traditionally limited to supportive measures such as rest and pain control, which remains the cornerstone. The role of corticosteroids remains controversial in this condition as its effectiveness and utility are not widely understood. This case highlights the unconventional use of corticosteroids in the management of refractory diabetic myonecrosis, emphasizing their potential in mitigating inflammation and promoting recovery.Case reportWe present a 31-year-old woman with ESKD on hemodialysis and a history of type 1 diabetes who presented with recurrent, debilitating pain and swelling in the right lower extremity. Despite a comprehensive workup, including MRI and a muscle biopsy confirming myonecrosis, the patient’s symptoms persisted despite conventional supportive care. Following a multidisciplinary discussion, corticosteroid therapy was initiated, resulting in dramatic symptom resolution within 48 h. The patient experienced significant pain reduction, improved mobility, and decreased swelling, allowing for discharge on a tapered steroid regimen. Notably, a subsequent recurrence of myonecrosis in a different muscle group also responded favorably to corticosteroid treatment, further underscoring its therapeutic potential in the management of patients with this condition.Discussion/conclusionThis case underscores the importance of considering corticosteroids as an adjunctive therapy in refractory diabetic myonecrosis, particularly in patients who fail to respond to standard care. A detailed workup, a high degree of suspicion, distinct clinical findings, and imaging such as MRI, along with muscle biopsy, can accurately diagnose this condition. While corticosteroids are not routinely used due to their potential risks, their dramatic effect in this patient highlights the need for further research to better understand their role and to refine treatment strategies. By expanding the therapeutic approach to diabetic myonecrosis, this case provides valuable insights for improving outcomes in this rare and challenging condition. This case opens the door for the exploration of corticosteroids as an adjunctive therapy in similar diabetic patients with ESKD and refractory myonecrosis.